Agency and Disempowerment in an EAP/EFL Context: Vignettes from a village high school in the Philippines - Fontejon-Bonior, Gina A. (Silliman Journal, 2023)
This article presents the observations and generalizations I made in the research I conducted in a Philippine village high school three years ago. Framing this discussion are the limitations of the research acknowledging my position as a neophyte ethnographer and my positionality as a participant observer, i.e., someone who grew up in the research site, who immerses herself in the activities of the observed community and continually reflects on her subjectivities as a researcher in such position, and who encourages other research participants to collaborate in the data collection and interpretation. This article is segmented into three parts: (1) the context of study, (2) the observations I made as a participant-observer, and (3) the analysis of recurrent patterns that presented themselves significant for analysis. Such patterns were on three areas: a) the limited agency of students, teachers, and administrators; b) the silencing of critical voices; and c) the paradoxical role of English as socio-economic equalizer and stratifier of students in Philippine context where English, the language of a colonizing power, remains as the medium of instruction in a post-colonial era.